(3GdUMI GdfaSjI (B=s Mental health - (3TMGJI, MSf CMeOs; (3UdGM, eQhIs; (3YHO GdQGRb, hdGA eMeOs ((3GdefhajI, eUQs (3MhGOjJ ddfTQ hGdJhRjYs, 2024)
(3Ef GdUMI GdfaSjI djSJ abW Ndh GdLSe hGdfaS ef GdCeQGV hMGdGJ GdYLR, Hd gj MGdI ef CcJeGd GdSdGeI GdLSOjI hGdYbdjI hGdfaSjI hGdGLJeGYjI habG dJYQja efXeI GdUMI GdYGdejI, aGdUMI GdfaSjI MGdI ef GdYGajI JSeM ddaQO HEOQGc EecGfGJg hGdJcja eY MGdGJ GdJhJQ GdGYJjGOjI hJecfg CjVG ef GdYed HEfJGL haGYdjI hGdESgGe aj eLJeYg hHjFJgs
Keywords: (3GdGVWQGHGJ GdfaSjIs; (3GdUMI GdfaSjIs; (3GdYdGL GdfaSjs